A Note on Zinbiel Algebras (Communications in Mathematical Research, 2021)
In this paper, we consider the decomposition of Zinbiel algebras with aspecial bilinear form which are called quadratic Zinbiel algebras. We obtain that thedecomposition into irreducible ideals of a quadratic Zinbiel algebra is unique underan isometry.